Tantalum doping in HfO2: orthorhombic phase formation at ambient conditions and change in path of pressure-induced structural evolution. Issue 3 (2nd July 2020) - Pathak, S.; Das, P.; Sahu, M.; Pandey, K. L.; Mandal, G.; Patkare, G. R.
ABSTRACT: A systematic study of orthorhombic phase formation at ambient conditions beyond a critical concentration of dopant Tantalum (Ta) in HfO 2 is reported. The effect on the path of structural evolution due to Ta doping in HfO 2 was also investigated. Studies on Ta-doped HfO 2 samples and their path of structural evolution under compression have significant implications for materials undergoing β -decay. The effect of continual doping due to β -decay from geophysical point of view is discussed.